Aplikasi GIS dan Simulasi Banjir Sungai Siak Pekanbaru Menggunakan XP-SWMM - Yusri, Yusri; Karim, Othman A.; Toriman, Mohd. Ekhwan; Kamarudin, Mohd. Khairul Amri (Jurnal Semesta Teknika, 2009)
Pekanbaru, the capital of Riau province, consists of 12 localities and covering an area of 632.26 square kilometer. The current land utilization in this city may create sufcare hydrology problems, such as flooding and shortage of water. The objective of this work is to analyse the land utilization pattern in Pekanbaru in 2004 in conjunction with flooding problem. The ArcView GIS 3.2 software package was implemented to analyse the land utilization data provided by a satelite, and the XP-SWMM hydrodynamic software package was used to simulate the flooding of Siak river in Pekanbaru. The result showed that land utilization was dominated for farming (49.26%), followed by vegetation, forestry, and settlement (17.09%, 13.06% and 11.97%, respectively). The simulation revealed that the flood occured in 28 December 2004 had submerged three regions, i.e. Sri Meranti, Meranti Pandak, and Pesisir, covering an area of approximately 880 hectare. In addition to this, bigger floods had been predicted to occure in the near future if the utilization of land is not pecisely managed.